Roundup™ With Corticosterone Functions as an Infodisruptor to Antipredator Response in Tadpoles - Gabor, Caitlin R.; Perkins, Hannah R.; Heitmann, Austin T.; Forsburg, Zachery R.; Aspbury, Andrea S. (Frontiers in Ecology and Evolution, 2019)
Larval amphibians are frequently exposed to multiple stressors in aquatic environments, so understanding how individual stressors and synergisms of multiple stressors affect amphibians is integral to conservation efforts. Glyphosate, the active ingredient in Roundup, is a common pollutant found in aquatic environments. Exposure to glyphosate induces morphological, behavioral, and physiological changes in tadpoles possibly via infodisruption. Urban aquatic environments may have environmentally relevant levels of glyphosate, as well as higher concentrations of exogenous corticosterone (CORT) than rural areas. Elevated CORT levels also affect the morphology and physiology of tadpoles. Dragonfly larvae are common predators of tadpoles, and tadpoles often show elevated CORT and reduced activity in the presence of dragonfly larvae. We tested the hypothesis that combined effects of exogenous CORT and Roundup exposure would affect the antipredator behavior, morphology, and stress hormone responses of Gulf coast toad, Incilius nebulifer, tadpoles. We exposed tadpoles to one of four treatments: Roundup, CORT, Roundup+CORT, or control, for 7 days. Tadpoles exposed to CORT or Roundup+CORT had elevated CORT release rates. Tadpoles exposed to exogenous CORT had lower tail depth compared to tadpoles in other treatments. Subsequently, we exposed tadpoles to dragonfly diet cues. Tadpoles increased activity after predator cue exposure when they had previously been exposed to Roundup+CORT. Taken together, our results suggest that there may be synergistic effects between Roundup and exogeneous CORT on organismal behavior but not their physiology or morphology. It appears that glyphosate is an infordisruptor, that prevents tadpoles from demonstrating adaptive antipredator responses, which may contribute to population declines.